Neotectonic movement in the southern margin of the Ordos Block inferred from the Qianhe River terraces near the north of the Qinghai–Tibet Plateau. (17th January 2018) - Chen, Shu‐E; Fan, Shuang‐Hu; Wang, Xiao‐Zhao; Wang, Ren‐Peng; Liu, Yi‐Liang; Yang, Liu‐Chen; Ning, Xiao‐Hong; Li, Rongxi
Abstract : The Qianhe River flows between the Liupanshan Orogen and the Ordos Block, with the river valley controlled by the southern margin fault of the Ordos Block. Five asymmetrical terraces exist on the banks of the Qianhe River, which correspond to the five terraces of the Wei River. Each terrace is composed of alluvial deposits at the bottom beneath loess deposits, which are characterized by alternating loess (L) and paleosol (S) layers, with the basal layers of the loess deposits being S0, S1, S5 3, S8, and L15 from T1 to T5. The heights of the five terraces T5, T4, T3, T2, and T1 are 220 to 260 m, 130 to 160 m, 60 to 80 m, 20 to 30 m, and 8 to 10 m, respectively, above the present valley, and their ages are 1.2, 0.8, 0.5, 0.13, and 0.01 Ma, respectively. These ages are generally consistent with the several uplift periods of the Qinghai–Tibet Plateau in the medium and late stages. Therefore, neotectonic movement is the controlling factor of river terrace formation in the periphery of the Ordos Block. According to the south‐west movement of the river channel in the lower reaches of the Qianhe River, it can be estimated that the Ordos Block rotated about 20° counterclockwise in the Pleistocene.